2019
DOI: 10.32479/ijeep.7712
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oil Prices on Inflation: The Case of Azerbaijan

Abstract: This paper investigates the relationship between inflation, oil prices and exchange rate in Azerbaijan using the vector error correction model (VECM) to the data ranging from 1995 to 2017. The results from cointegration method confirm the existence of a long-run relationship among the variables. Moreover, estimation results of VECM show that the oil prices and exchange rate have positive and statistically significant impact on inflation in the long-run. This implies that 1% increase in oil prices and exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 19 publications
5
37
0
1
Order By: Relevance
“…In the case of Azerbaijan, prior research conducted by Mukhtarov et al (2019c) examined the oil prices effect on inflation by employing the Vector Error Correction Model (VECM) to the data ranging from 1995 to 2017. Authors found that the oil prices have a positive and statistically significant impact on inflation in the long-run.…”
Section: The Impact Of Oil Prices On Exchange Ratementioning
confidence: 99%
“…In the case of Azerbaijan, prior research conducted by Mukhtarov et al (2019c) examined the oil prices effect on inflation by employing the Vector Error Correction Model (VECM) to the data ranging from 1995 to 2017. Authors found that the oil prices have a positive and statistically significant impact on inflation in the long-run.…”
Section: The Impact Of Oil Prices On Exchange Ratementioning
confidence: 99%
“…Before this date, the tax farming system, which prevented the development of the oil industry, was abolished. After this development, the participation of foreign capital, on the one hand, and the expansion of the oil geography in Absheron, on the other hand, the acceleration of oil production and the development of oil production techniques were ensured in creating favourable conditions for the growth of the oil industry [22] These lands were mostly leased by Russian and Armenian investors. It is observed that Azerbaijani H. Z. Tagiyev was among the lessees.…”
Section: The History Of Oil and Natural Gas In The Caspian Seamentioning
confidence: 99%
“…Some may call these views conspiracy theories. However, the whole world is watching with horror how the strong exert their authority over the weak [22]. The instances of Iraq and Kuwait stand out as very recent examples.…”
Section: Reserve Amount Of Caspian Oilmentioning
confidence: 99%
“…Doğal kaynak tabanlı milli gelir artışı ile reel döviz kurunun değerlenmesi, ithalat artışının yanı sıra düşük faiz oranına ve enflasyon artışına sebep olmaktadır. Rusya Federasyonu (Ito, 2008b), İran (Abounoori, Nazarian & Amiri, 2014), Kazakistan (Köse & -170 - Baimaganbetov, 2015), Vietnam (Trang, Tho & Hong, 2017), Meksika (Delgado, Delgado & Saucedo, 2018) ve Azerbaycan (Mukhtarov, Mammadov & Ahmadov, 2019) için yapılan çalışmalar, petrol geliri ile enflasyon arasında dolaylı bir ilişki olduğunu; petrol gelir artışının kamu harcamalarını ve yatırımlarını artırdığını ve bunun daha yüksek fiyatlara yol açtığını belirtmektedir. Ancak Ito (2010) yine Rusya Federasyonu için farklı olarak petrol gelirlerindeki artışın fiyatlar üzerine tam tersi etkisi olduğunu göstermektedir.…”
Section: Petrol İhracatçısı üLkelerin Ekonomik Performanslarını İnceleyen çAlışmalarunclassified